Al-Zaytun the untold stories : investigasi terhadap pesantren paling kontroversial di Indonesia - Indonesian Institute for Society Empowerment (Kramat Jati, Jakarta : Kerjasama antara Alvabet [dan] Lembaga Kajian Islam & Perdamaian, 2011)
On Ma'had al-Zaytun, an Islamic religious education center related to Islamic state.
Includes bibliographical references (p. 219-229).
In Indonesian.
Keywords: Ma'had al Zaytun; Islamic religious education -- Indonesia; Islam and state -- Indonesia